Relationship of bruxism with oral health-related quality of life and facial muscle pain in dentate individuals - Turcio, Karina Helga Leal [UNESP]; Melo Neto, Clóvis-Lamartine de Moraes [UNESP]; Pirovani, Beatriz-Ommati [UNESP]; Santos, Daniela Micheline dos [UNESP]; Guiotti, Aimée Maria [UNESP]; Bertoz, André Pinheiro de Magalhães [UNESP]; Brandini, Daniela Atili [UNESP] (Medicina Oral, S.L., 2022)
Background: To determine whether there is a correlation of bruxism (sleep, daytime, or both) with oral health-related quality of life and facial pain of muscular origin in dentate individuals. Materials and Methods: Seventy-four dentate patients (complete dentition) were included in this study. These individuals had pain in the facial muscles due to temporomandibular disorder (TMD). Smokers; and those with obstructive sleep apnea, TMD of joint origin associated or not with pain, malocclusion, and cancer; and users of illicit drugs, psychiatric medications, and alcohol were excluded. Obstructive sleep apnea, bruxism (of sleep and/or daytime), facial muscle pain, and oral health-related quality of life were assessed by the following questionnaires: Berlin Questionnaire, Pintado et al. questionnaire, VAS (Visual Analog Scale) facial muscle pain questionnaire, and Oral Health Impact Profile – 14. Four groups were created: 1) no bruxism; 2) sleep bruxism; 3) daytime bruxism; and 4) sleep and daytime bruxism. Spearman’s correlation test was applied to verify if there was a correlation between the collected data. P values less than 0.05 were considered statistically significant. Results: There was a positive correlation of daytime bruxism with mean pain in the last 3 months (P<0.05) and the worst pain experienced in the last 3 months (P<0.05). Conclusions: Bruxism (sleep, daytime, or both) showed a positive correlation with lower oral health-related quality of life (P<0.05)
Keywords: Bruxism; Facial pain; Health-related quality of life; Surveys and questionnaires; Temporomandibular joint disorders